Movement and Aggregation of Eastern Hudson Bay Beluga Whales (Delphinapterus leucas): A Comparison of Patterns Found through Satellite Telemetry and Nunavik Traditional Ecological Knowledge - Lewis, A. E.; Hammill, M. O.; Power, M.; Doidge, D. W.; Lesage, V. (ARCTIC, 2009)
Traditional Ecological Knowledge (TEK) consists of the collective knowledge, experience, and values of subsistence communities, while Western science relies on hypothesis testing to obtain information on natural processes. Both approaches provide important ecological information, but few studies have directly compared the two. We compared information on movements and aggregation of beluga whales obtained from TEK interview records (n = 3253) and satellite telemetry records of 30 whales tagged in eastern Hudson Bay, Canada, using geographic information system (GIS) approaches that allowed common formatting of the data sets. Estuarine centres of aggregation in the summer were evident in both data sets. The intensive use of offshore areas seen in the telemetry data, where 76% of the locations were more than 15 km from mainland Quebec, was not evident in the TEK data, where only 17% of the records indicated offshore locations. Morisita’s index of similarity indicated that TEK and telemetry data distributions varied with season, with the highest similarity in winter (0.74). Location and movement data from the telemetry study were limited by small sample size and short tag deployment times, while TEK data were biased by spatial coverage and coastal travel habits. Although the two data sets can provide complementary information, both suffer from weaknesses that need to be acknowledged when these data are adapted for use in resource management. Les connaissances écologiques traditionnelles (CÉT) consistent en l’ensemble des connaissances, de l’expérience et des valeurs des communautés de subsistance, tandis que la science occidentale s’appuie sur la mise à l’épreuve d’hypothèses dans le but d’obtenir de l’information sur les processus naturels. Bien que ces deux démarches permettent d’obtenir d’importants renseignements sur l’écologie, peu d’études ont établi une comparaison directe entre ces deux démarches. Nous avons comparé des données sur les mouvements et le rassemblement des bélugas, données obtenues à partir de ...